S104 Communication between infection experienced lung stromal cell subsets and resident immune cells is altered in the influenza virus infected lung. (11th November 2022) - Worrell, JC; Finney, GE; Hargrave, KE; Hansell, C; Nijjar, JS; Morton, F; Cole, J; MacLeod, MKL
Abstract : Introduction and Objectives: Influenza A virus (IAV) infections are a significant cause of mortality worldwide. The concept that stromal cells are permanently altered by insults is termed trained immunity. Whether these cells contribute to protection or pathology is unclear. We hypothesise that trained stromal cells may participate in protective immune responses by rapidly reactivating local memory T cells. Methods: C57BL/6 mice were infected intranasally with IAV (WSN, 150PFU) for 30 days and subsequently re-challenged with IAV (X31, 200PFU) for either 2 or 5 days. Mice were sacrificed at day 0, 2, 5, 30, 32, 35 post infection. To detect infected cells, ex vivo, IAV-Nucleoprotein (NP) expression was measured using flow cytometry and the location of NP+ stromal cells was determined using immunofluorescence. Further phenotyping of infection experienced stromal cell subsets was conducted using RNA-scope, immunohistochemistry, and qPCR. To assess the consequences of T cell depletion on NP expression by lung stromal cells following IAV re-challenge, anti-CD4/CD8 blockade was performed during the memory phase of infection. Results: Following influenza virus infection, NP+ epithelial cells were detected at primary (day 2, 5) and to a lesser extent at recall timepoints (day 32, 35). Importantly, NP+ epithelial cells expressed more MHCII compared to NP-negative cells, suggesting enhanced capability to communicate with T cells via enhanced antigen processing/presentation. Using RNAscope, SpiB, a transcription factor that regulates genes involved in antigen processing/presentation, was detected in lung epithelial cells of infected mice. SpiB+ cells were in close proximity to immune cells that form dense clusters containing a mixture of T/B cells and myeloid populations. Interestingly, these microenvironmental changes were dependent on viral replication. Increased frequencies of Ki67+ lung fibroblasts coincided with significant increases in interferon-responsive fibroblasts at early timepoints post infection, compared to naive controls. These two fibroblasts populations did not express NP. Following IAV re-challenge both fibroblast subsets were reduced compared to primary timepoints, suggesting high numbers of infected cells may be required to promote their expansion post infection. Conclusions: Infection experienced stromal cell subsets may promote immune protection upon re-infection, through antigen presentation to T cells and/or alteration of the local lung microenvironment. Please refer to page A211 for declarations of interest related to this abstract.